Axmedis 2005 Proceedings of the 1st International Conference on Automated Production of Cross Media Content for Multi-channel Distribution. Volume for Workshops, Industrial and Applications Sessions. Florence, Italy, 30 November-2 December 2005 - Delgado, Jaime; nesi, paolo; Ng, Kia (Proceedings e report, 2005)
The AXMEDIS conference aims to promote discussions and interactions among researchers, practitioners, developers and users of tools, technology transfer experts, and project managers, to bring together a variety of participants. The conference focuses on the challenges in the cross-media domain (which include production, protection, management, representation, formats, aggregation, workflow, distribution, business and transaction models), and the integration of content management systems and distribution chains, with particular emphasis on cost reduction and effective solutions for complex cross-domain problems.